Electronic devices for monitoring water pH, Humidity, and Temperature control in Agro-Hydroponic Businesses - Firmansyah, M.Erdian; Muskhir, mukhlidi; Mukhaiyar, Riki; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Increasing the cultivation of hydroponic plants presents challenges, particularly in monitoring water pH and controlling temperature and humidity in hydroponic farming, which are often neglected. The lack of proper monitoring can significantly impact hydroponic plant growth. This issue arises due to the reliance on manual checks, which prevents real-time and efficient monitoring. This research employs a comparative method to analyze water pH levels using both a water pH sensor and a pH meter. For temperature and humidity monitoring in the hydroponic plant area, the study compares the readings of the DHT22 sensor with online weather data, both monitored anytime via a web server. Temperature and humidity data can be accessed at any time, but the focus of comparison is on daytime, as temperature and humidity fluctuations are more drastic, with temperatures exceeding 30°C. The purpose of this test is to determine the water pH level as well as the temperature and humidity conditions suitable for hydroponic farming. Based on observations, the developed system enables real-time monitoring via a web server, demonstrating good performance and meeting efficiency objectives in automated temperature and humidity control. The implementation of this system is expected to be expanded in the future, providing a viable solution for users and enhancing process efficiency in related fields